Identifikasi Faktor yang Mempengaruhi Pemerintah Desa dalam Pengelolaan Sanitary Landfill di Desa Tungkal Selatan Kecamatan Pariaman Utara Kota Pariaman - Rizki Khairani, Syabahul; Yusran, Rahmadani (Policy, Law and Political Research Center, 2023)
This study intends to identify influencing factors in the Implementation of Village Government in Sanitary Landfill Management in South Tungkal Village, North Pariaman District, Pariaman City. This research uses a semi-qualitative approach. A purposive sampling approach was used in this study to identify research informants. For data collection techniques, it is carried out with interviews and observations and documentation. For data analysis techniques using data reduction and data presentation and drawing conclusions. The results showed that there are influencing factors, namely: (1) Human resources that support the management of sanitary landfills. For human resources, the Environment Agency has 87 cleaning members consisting of drivers, stokars and 46 other members. (2) Second, a supportive commitment to the management of Sanitary Landfill. The form of commitment made provides budget and human resources to carry out the management of this Sanitary Landfill. (3) Third, community support and participation for sanitary landfill management. The community does not want to liberate land because the land has the status of customary land or customary land. (4) Fourth, the budget and tools are limited for the management of Sanitary Landfills. In Sanitary Landfill, the Environment Agency requires a budget for infrastructure and a human resources budget.